2017
DOI: 10.1002/star.201700030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of additives on mechanical and barrier properties of starch‐based films plasticized with deep eutectic solvents

Abstract: The aim of this work was to prepare starch‐based films plasticized with two and three‐component deep eutectic solvents (DES) in the presence of different additives: aluminosilicates (sodium and calcium montmorillonite), microcrystalline cellulose, and tannin; and to investigate their influence on mechanical and barrier properties of the films. Mutual interactions between polysaccharide matrix, plasticizer, and additive were investigated by Fourier transform infrared (FTIR) spectroscopy. Two types of starches w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…It was shown that a glycerol imidazole mixture modified the surface of the wood fibres and exhibited better adhesion than the other plasticizers presented in this work. Zdanowicz and Johannson [35] used potato starch plasticized with two or three component DESs to obtain composites with various natural fillers: sodium and calcium montmorillonite, nitrocellulose and tannin. Starch-based films were prepared via the casting method.…”
Section: Dess For Starch Plasticizationmentioning
confidence: 99%
“…It was shown that a glycerol imidazole mixture modified the surface of the wood fibres and exhibited better adhesion than the other plasticizers presented in this work. Zdanowicz and Johannson [35] used potato starch plasticized with two or three component DESs to obtain composites with various natural fillers: sodium and calcium montmorillonite, nitrocellulose and tannin. Starch-based films were prepared via the casting method.…”
Section: Dess For Starch Plasticizationmentioning
confidence: 99%
“…In summary, only few works have focused so far on starch dissolution with DESs. A primary focus has been given towards the study of the plasticization of starch with these solvents to improve the mechanical properties of thermoplastic polymers [ 222 , 223 ]. However, an increasing knowledge behind starch dissolution mechanisms in DESs is expected to come in the near future.…”
Section: Starchmentioning
confidence: 99%
“…Preparation of starch-based films with DESs and different additives (sodium and calcium montmorillonite, tannin and microcrystalline cellulose) was performed by Zdanowicz and Johansson. [38] In film preparation, two different DESs are used (ChCl : glycerol and CCit : urea : glycerol) combined with starch and various mentioned additives. Elongation at break for films containing ChCl : glycerol was in the range from 29.2 to 78.5 % while much lower values were noticed in the case of films with CCit : urea : glycerol (5.1 -29.7 %).…”
Section: Starch-based Filmsmentioning
confidence: 99%